Pengaruh Kualitas Pelayanan, Membership, Dan Harga Terhadap Keputusan Pembeli Pada Vape Move Ngawi - Affan Nailul Fajar Alwani; Endang Edi Rahaju; Hartirini Warnaningtyas (Universitas Merdeka Madiun, 2022)
This study aims to examine and determine the effect of partially or simultaneously service quality, membership, and price on buyer decisions on Vape Move Ngawi. This research is an explanatory research using a quantitative approach. The samples taken in this study were 100 consumers as regular customers who bought products on Vape Move Ngawi. This research uses purposive sampling method. That is the sampling technique by setting special characteristics or special conditions with the aim of being able to answer the research statement. The data collection method used is a questionnaire distributed to 100 consumers as regular customers. The data analysis technique used classical assumption test, multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing using t test and F test with the help of IBM SPSS Statistics 25 program. The results showed that (1) service quality, membership, and price were overall partial significant effect on the decision of product buyers on Vape Move Ngawi. (2) Simultaneously shows that service quality, membership, and price have a significant effect on buyer decisions on Vape Move Ngawi.